2017
DOI: 10.7554/elife.15085
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the opposing effects of G6PD deficiency on cerebral malaria and severe malarial anaemia

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is believed to confer protection against Plasmodium falciparum malaria, but the precise nature of the protective effect has proved difficult to define as G6PD deficiency has multiple allelic variants with different effects in males and females, and it has heterogeneous effects on the clinical outcome of P. falciparum infection. Here we report an analysis of multiple allelic forms of G6PD deficiency in a large multi-centre case-control study of severe malaria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 63 publications
5
92
0
Order By: Relevance
“…Epitomal in this respect is the case of FUT2 described above, as well as that of ABO: individuals with O histoblood group are protected against severe malaria and cerebral malaria, but at higher risk of developing highly symptomatic cholera infection (Malaria Genomic Epidemiology Network and Malaria Genomic Epidemiology Network, 2014;Cooling, 2015). Interestingly, large-scale studies that focused on specific variants involved in resistance to malaria (Malaria Genomic Epidemiology Network and Malaria Genomic Epidemiology Network, 2014;Clarke et al, 2017) indicated that G6PD deficiency also results in different susceptibility phenotypes. Thus, the level of G6PD activity is associated with decreased risk of cerebral malaria, but with increased risk of severe malarial anaemia (Malaria Genomic Epidemiology Network and Malaria Genomic Epidemiology Network, 2014;Clarke et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epitomal in this respect is the case of FUT2 described above, as well as that of ABO: individuals with O histoblood group are protected against severe malaria and cerebral malaria, but at higher risk of developing highly symptomatic cholera infection (Malaria Genomic Epidemiology Network and Malaria Genomic Epidemiology Network, 2014;Cooling, 2015). Interestingly, large-scale studies that focused on specific variants involved in resistance to malaria (Malaria Genomic Epidemiology Network and Malaria Genomic Epidemiology Network, 2014;Clarke et al, 2017) indicated that G6PD deficiency also results in different susceptibility phenotypes. Thus, the level of G6PD activity is associated with decreased risk of cerebral malaria, but with increased risk of severe malarial anaemia (Malaria Genomic Epidemiology Network and Malaria Genomic Epidemiology Network, 2014;Clarke et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, large-scale studies that focused on specific variants involved in resistance to malaria (Malaria Genomic Epidemiology Network and Malaria Genomic Epidemiology Network, 2014;Clarke et al, 2017) indicated that G6PD deficiency also results in different susceptibility phenotypes. Thus, the level of G6PD activity is associated with decreased risk of cerebral malaria, but with increased risk of severe malarial anaemia (Malaria Genomic Epidemiology Network and Malaria Genomic Epidemiology Network, 2014;Clarke et al, 2017). Moreover, by using a Bayesian statistical framework that allows for heterogeneity of effects across populations and phenotypes, the authors showed that homozygotes for the derived allele of a variant in the 5′ upstream region of CD40LG have significantly reduced risk of severe malaria in The Gambia, but significantly increased risk in Kenya (Malaria Genomic Epidemiology Network and Malaria Genomic Epidemiology Network, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…All of these differences are compounded by the fact that many of the studies use different definitions of clinical malaria, which makes it difficult to draw conclusions and compare studies. To address this problem, a recent sub‐study from a large multi‐centre case–control study of severe malaria (Malaria Genomic Epidemiology Network, ) reported an analysis of multiple allelic forms of G6PD deficiency in 11 countries from Africa and Asia using a set of 135 single nucleotide polymorphisms (Clarke et al , ). This study reported that increasing levels of G6PD deficiency are associated with decreasing risk of cerebral malaria, but with increased risk of severe malarial anaemia.…”
Section: Enzymatic Deficienciesmentioning
confidence: 99%
“…G6PDH deficiency is the most common human enzymatic defect disorder; it causes hemolytic anemia triggered by the exposure of red blood cells to oxidant agents [1]. Despite this negative effect, G6PDH deficiency confers some level of resistance against malaria, being found in higher frequency in regions where malaria is endemic [2]. Although G6PDH is considered a 'housekeeping' enzyme, its expression level, intracellular translocation, and post-translation (phosphorylation) modification have been demonstrated to be regulated, both positively and negatively, by different signaling factors (revised by Stanton, 2010 [3]).…”
mentioning
confidence: 99%